PEMANFAATAN ZEOLIT ALAM UNTUK PENGERINGAN KARAGINAN DENGAN SPRAY DRYER - Babar Priyadi M.H; Thufail Khoirul Afifi; Setia Budi Sasongko (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
The problem that will be faced in drying is quite high relative humidity, therefore carrageenan drying process using spray dryer with zeolite as humidity absorber becomes alternative option to achieve heat effectiveness of air dryer. The research is purposed to examine the effect of temperature and level of zeolite to relative humidity and product quality on carrageenan drying process. Spray dryer is a dryer used to produce powder material from feeds which have liquid and pasta form. The Results indicate that humidity and carrageenan product quality are influenced by drying air temperature and zeolite level. Zeolite absorber will influence humidity. The higher zeolite level is, the lower humidity will be. when zeolite level 25 cm, the initial relative humidity is about 70%. It will be decrease until 27% and the drying air temperature before heater gets increase from 28ᵒC to 42ᵒC. The higher drying air temperature and zeolite level are, the better quality of carrageenan product will be. When drying air temperature is 90 ᵒC and zeolite level is 25 cm, moisture content of carrageenan product is 30,17% and the highest product efficiency is 68,67%. Carrageenan product efficiency gets increase by increasing drying air temperature and zeolite level.